Discovery of evocalcet, a next-generation calcium-sensing receptor agonist for the treatment of hyperparathyroidism. Issue 11 (15th June 2018) - Miyazaki, Hiroshi; Ikeda, Yousuke; Sakurai, Osamu; Miyake, Tsutomu; Tsubota, Rie; Okabe, Jyunko; Kuroda, Masataka; Hisada, Yutaka; Yanagida, Tetsuya; Yoneda, Hikaru; Tsukumo, Yukihito; Tokunaga, Shin; et al.
Graphical abstract: Highlights: Optimization from cinacalcet resulted in the discovery of evocalcet. CYP2D6 inhibition observed in cinacalcet is completely solved in evocalcet. Gastrointestinal tract symptoms of cinacalcet are drastically improved in evocalcet. Evocalcet will provide a novel therapeutic option for secondary hyperparathyroidism. Abstract: The calcium-sensing receptor (CaSR) plays an important role in sensing extracellular calcium ions and regulating parathyroid hormone secretion by parathyroid gland cells, and the receptor is a suitable target for the treatment of hyperparathyroidism. Cinacalcet hydrochloride is a representative CaSR agonist which widely used for the hyperparathyroidism. However, it has several issues to clinical use, such as nausea/vomiting and strong inhibition of CYP2D6. We tried to improve these issues of cinacalcet for a new pharmaceutical agent as a preferable CaSR agonist. Optimization from cinacalcet resulted in the identification of pyrrolidine compounds and successfully led to the discovery of evocalcet as an oral allosteric CaSR agonist. Evocalcet, which exhibited highly favorable profiles such as CaSR agonistic activity and good DMPK profiles, will provide a novel therapeutic option for secondary hyperparathyroidism.